Moderasi Beragama sebagai Kekhasan Hidup Berbangsa: Studi Reflektif Dalam Perjumpaan Hinduisme Dalam Penghayatan Kebatinan Dalam Budaya Jawa - Kinasih, CL Tindra Matutino (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2022)
Sometimes in life it is easy for people to blame others, any circumstances or objects are easy to blame. Envy, jealousy, suspicious are traits that are currently often seen in social phenomena. 2022 as a year of moderation is considered a utopian ideal for some, and others are optimistic about achieving it. The problem is what causes us to be pessimistic or optimistic about achieving it? In this study, I use a reflective study to look at the basis of Indonesian human life by reflecting on the Encounter of Hinduism in Penghayatan Kebatinan in Javanese Culture. People who have been able to find the true essence in themselves then that person will get salvation. When people have found themselves, people will accept others. By being able to accept others, then the hope of tolerance can be realized. The life history of the Javanese is a witness to how the moderation movement as an embodiment of national dignity has become a basis that has been lived for a long time. The moderation movement is something that is far and away from Indonesia. From this narrative and writing, it can be seen that moderation is a form of dignity and the breath of national life. Openness to external elements without authenticity is a manifestation of the dignity of Life. The ideal of maintaining harmony is the basic philosophy of Javanese people in living life.